2010
DOI: 10.1037/a0019036
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of stress autonomy versus stress sensitization in adolescents at varied risk for depression.

Abstract: This longitudinal study investigated the stress autonomy, stress sensitization, and depression vulnerability hypotheses in adolescents across six years (i.e., grades 6 through 12). Participants were 240 children (Time 1 mean age = 11.86, SD = 0.57) who varied in risk for depression based on their mother's history of mood disorders. All analyses were conducted as multilevel models to account for nesting in the data. Results were consistent with the stress sensitization hypothesis. The withinsubject relation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 87 publications
8
61
0
2
Order By: Relevance
“…For instance, adolescents may become more sensitive to stress after having experienced child abuse or previous episodes of mental illness (Monroe & Harkness, 2005;Morris, Ciesla, & Garber, 2010;Stroud, Davila, & Moyer, 2008). The relationships between vulnerability and stress are further complicated by the observation that past stressors may increase not only sensitivity to future stress, but also exposure to it, in a process of stress generation (Hammen, 2006;Liu & Alloy, 2010).…”
Section: The Stress Process As a New Angle To Look At Dropoutmentioning
confidence: 99%
“…For instance, adolescents may become more sensitive to stress after having experienced child abuse or previous episodes of mental illness (Monroe & Harkness, 2005;Morris, Ciesla, & Garber, 2010;Stroud, Davila, & Moyer, 2008). The relationships between vulnerability and stress are further complicated by the observation that past stressors may increase not only sensitivity to future stress, but also exposure to it, in a process of stress generation (Hammen, 2006;Liu & Alloy, 2010).…”
Section: The Stress Process As a New Angle To Look At Dropoutmentioning
confidence: 99%
“…It has been proposed that the augmented prevalence of depression among adolescents, compared to preadolescents, may be attributed to sensitization (Morris, Ciesla, & Garber, 2010). Adolescents, due to psychobiological potentiation effects, are more vulnerable to uncontrollable stressful situations and subsequently more predisposed for negative affect (Chorpita & Barlow, 1998).…”
Section: Depression and Stress In Adolescencementioning
confidence: 99%
“…However, there are large individual differences in how well people handle life stressors. Indeed, problems with stress regulation are thought to play a central role in the development and clinical course of depression (Hooley, Orley & Teasdale, 1986;Hankin, 2008;Morris, Ciesla & Garber, 2010). It has also been suggested that, over time, depressive episodes can be triggered by progressively milder and milder stressors (Monroe & Harkness, 2005; but see also Anderson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%